A reflection on practice-related research – the case of radio journalism. (1st September 2017) - Coleman, Josephine
A reflection on conducting and articulating practice-related research, based on a reading of the article entitled 'Radio journalism as research – a Ph.D. model', by Mia Lindgren (2014) in The Radio Journal – International Studies in Broadcast & Audio Media, 12:1&2, pp. 169–182. Lindgren's case study was her Ph.D. thesis, 'Journalism as research: Developing radio documentary theory from practice' (2011), Murdoch University, Perth.